The protean ptyx: nonsense, non-translation and word magic in Mallarme's 'Sonnet en yx' - Duncan, D (Oxford University Press, 2019)
This chapter presents an extensive analysis of questions of translation and non-translation through the focal point of Stéphane Mallarmé’s ‘Sonnet en yx’. It traces early responses to this poem that highlighted the challenge to interpretation posed by ‘ptyx’: was this a nonsensical neologism or an untranslated derivation from another language? The chapter shows how the term resonated with other artists and moved ‘from the category of the untranslated to the untranslatable’. The term exemplifies a kind of ‘word magic’ that modernism conjures out of non-translation, a quasi-mysticism of unfamiliar noises that prompts readers to dwell on formal and sonic capacities as well as the conceptual contours of language.